Integrated Taxonomy Discovers Four New Species of Grypoctonus Speiser, 1928 (Diptera: Asilidae) from China - Haoyue Zhou; Ding Yang; Xuankun Li (Insects)
The genus Grypoctonus Speiser, 1928 (Diptera: Asilidae) is a fuzzy-looking assassin fly, and adults have only been observed in autumn and winter. Currently containing four described species, this genus is readily distinguished from other Chinese asilids by the presence of two r-m crossveins. Through integrative taxonomic analysis of over 200 specimens from multiple Chinese provinces, we combined morphological assessment with DNA barcoding and four species delimitation methods (ABGD, ASAP, mPTP, and GMYC). Four species are newly described: G. aureus sp. nov., G. sagittatus sp. nov., G. solarius sp. nov., and G. yongshani sp. nov. (the latter described solely from morphological examination of historical specimens). Genetic analyses revealed distinct barcoding gaps, with an interspecific distance of 1.38–7.07% versus an intraspecific distance of no more than 0.92%. We revised the generic diagnosis, provided a distribution map, and a revised key to all known species of Grypoctonus.